2011
DOI: 10.1289/ehp.1003265
|View full text |Cite
|
Sign up to set email alerts
|

Isomer Profiles of Perfluorochemicals in Matched Maternal, Cord, and House Dust Samples: Manufacturing Sources and Transplacental Transfer

Abstract: Background: Perfluorochemicals (PFCs) are detectable in the general population and in the human environment, including house dust. Sources are not well characterized, but isomer patterns should enable differentiation of historical and contemporary manufacturing sources. Isomer-specific maternal–fetal transfer of PFCs has not been examined despite known developmental toxicity of perfluorooctane sulfonate (PFOS) and perfluorooctanoate (PFOA) in rodents.Objectives: We elucidated relative contributions of electroc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

28
149
12

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 175 publications
(189 citation statements)
references
References 41 publications
28
149
12
Order By: Relevance
“…In the present study, we found higher levels of PFCs in maternal serum than in cord serum, which is consistent with previous studies (Monroy et al 2008;Hanssen et al 2010;Beesoon et al 2011). Maternal and cord PFOS and PFOA concentrations were among the highest in Europe (Midasch et al 2007;Fei et al 2007;Needham et al 2011) and even among the highest in the world (Liu et al 2011;Kim et al 2011a, b;Beesoon et al 2011).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In the present study, we found higher levels of PFCs in maternal serum than in cord serum, which is consistent with previous studies (Monroy et al 2008;Hanssen et al 2010;Beesoon et al 2011). Maternal and cord PFOS and PFOA concentrations were among the highest in Europe (Midasch et al 2007;Fei et al 2007;Needham et al 2011) and even among the highest in the world (Liu et al 2011;Kim et al 2011a, b;Beesoon et al 2011).…”
Section: Discussionsupporting
confidence: 93%
“…Maternal and cord PFOS and PFOA concentrations were among the highest in Europe (Midasch et al 2007;Fei et al 2007;Needham et al 2011) and even among the highest in the world (Liu et al 2011;Kim et al 2011a, b;Beesoon et al 2011). Maternal and cord PFNA levels were lower than those measured in other countries (Monroy et al 2008;Needham et al 2011;Kim et al 2011a;Beesoon et al 2011). …”
Section: Discussionmentioning
confidence: 98%
“…Several studies have demonstrated a strong correlation between PFASs in maternal and umbilical cord blood, indicating that prenatal exposure of PFASs can occur through placental transfer (Beesoon et al 2011;ManzanoSalgado et al 2015;Midasch et al 2007). A recent systematic review summarized the evidence of an association between exposure PFASs and human fetal growth (Bach et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…It is still unclear what the potential impact of co-exposure of PFASs and isomer on the birth outcome or health effects in later life. To our knowledge, only two publications examined the concentration of PFASs and isomers in the umbilical cord blood: one was in South Africa with 58 cord serum (Hanssen et al 2010), and another was in Canada with 20 cord serum (Beesoon et al 2011). Given this tenuous state of the evidence, creation of isomer profiles in different geographic locations and populations is a high priority.…”
Section: Introductionmentioning
confidence: 99%
“…2,3,5 Recent studies showed that the ECF process was used to produce approximately 70% of linear PFASs and 30% of the branched isomers, whereas the telomerization process was mostly used to produce linear PFASs. 6,7 PFAA isomers have been ubiquitously found in the environment, in the biota, and even in humans, 7−13 and they show different properties in organisms, such as different halflives and bioaccumulation factors. 6 Previous studies on the basis of animal models indicated that linear and branched PFAA isomers have different elimination properties and toxicity.…”
Section: ■ Introductionmentioning
confidence: 99%